REGULATION OF SELF-DEFENCE IN SLOVENIAN AND INTERNATIONAL CRIMINAL LAW - Zgaga, Sabina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
This paper discusses the regulation of self-defence in Slovenian and international criminal law. Firstly the elements of self-defence in international criminal law are discussed. The paper also analyses the influence of self-defence on the general definition of a criminal act. This is followed by drawing the distinction between similar defences; self-defence and putative self-defence on one hand and self-defence and necessity on the other. Paper is concluded by presentation of Slovenian regulation of self-defence from the viewpoint of international criminal law.